2015
DOI: 10.1080/01694243.2015.1087256
|View full text |Cite
|
Sign up to set email alerts
|

Does 2% chlorhexidine digluconate cavity disinfectant or sodium fluoride/hydroxyethyl methacrylate affect adhesion of universal adhesive to dentin?

Abstract: Abstract:The objectives of this study were to investigate the adhesion of a universal adhesive used either in total-etch or self-etch mode with and without 2% chlorhexidine digluconate cavity disinfectant (CHX) or sodium fluoride/hydroxyethyl methacrylate (NaF/HEMA) to dentin. Dentin surfaces of extracted human non-carious third molar teeth (N=18) were exposed and randomly assigned to two groups. Half of the teeth were conditioned with total-etch and the other with self-etch adhesive mode. The teeth were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Most of the studies reported results on the application of cavity disinfectant agents such as chlorhexidine [ 12 , 13 , 14 , 15 , 16 , 17 , 23 , 24 , 26 , 27 , 36 , 39 , 42 , 53 , 56 , 57 , 61 , 62 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 73 , 75 , 77 , 79 , 81 , 86 , 87 , 88 , 90 , 91 , 98 , 100 , 102 , 103 , 104 , 105 , 111 , 113 , 122 , 123 , 124 , 126 , 128 , 132 , 133 , 134 , 135 , 137 , 142 , 143 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies reported results on the application of cavity disinfectant agents such as chlorhexidine [ 12 , 13 , 14 , 15 , 16 , 17 , 23 , 24 , 26 , 27 , 36 , 39 , 42 , 53 , 56 , 57 , 61 , 62 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 73 , 75 , 77 , 79 , 81 , 86 , 87 , 88 , 90 , 91 , 98 , 100 , 102 , 103 , 104 , 105 , 111 , 113 , 122 , 123 , 124 , 126 , 128 , 132 , 133 , 134 , 135 , 137 , 142 , 143 ,…”
Section: Resultsmentioning
confidence: 99%
“…Regarding its performance as a cavity disinfectant, chlorhexidine presented with positive results in the majority of the studies [ 16 , 17 , 24 , 36 , 39 , 42 , 53 , 56 , 57 , 61 , 62 , 65 , 66 , 67 , 68 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 86 , 87 , 90 , 91 , 98 , 100 , 102 , 103 , 104 , 105 , 111 , 113 , 122 , 123 , 124 , 128 , 132 , 134 , 135 , 137 , 142 , 143 , 148 , 153 , 157 ], allowing for maintenance or even an increase in bond strength values. On the other hand, a few authors [ 14 , 15 , 26 , 27 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative synthesis of the studies included in this systematic review are summarized in Table 2 . Several strategies were identified: Air abrasion [ 58 , 59 ], application of crosslinking agents [ 57 , 60 , 61 , 62 , 63 , 64 , 65 ], application of dentin desensitizers [ 66 , 67 ], use of matrix metalloproteinases (MMP) inhibitors [ 10 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], the use of the ethanol-wet bonding technique [ 78 ], application of an extra hydrophobic resin layer [ 56 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], dentin pretreatment with laser [ 55 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], multiple layer application [ 93 , 94 , 95 , 96 , 97 , 98 , 99 ], non-atmospheric plasma [ 100 , 101 ], prolonged curing time [ 102 ,…”
Section: Resultsmentioning
confidence: 99%
“…The reason is that weak acids possess the potential to activate the MMPs, particularly when their pH lies between 2.3 and 5, which is the case of many self-etch adhesives, making them very effective at activating gelatinase action [32]. Adhesion depends on the adhesive system used, with the non-simplified adhesive systems (etch and rinse) being more stable and effective than the simplified adhesive systems (self-etch) [44][45][46].…”
Section: Discussionmentioning
confidence: 99%